Effect of trait anxiety on prefrontal control mechanisms during emotional conflict. Issue 6 (9th February 2015) - Comte, Magali; Cancel, Aïda; Coull, Jennifer T.; Schön, Daniele; Reynaud, Emmanuelle; Boukezzi, Sarah; Rousseau, Pierre‐François; Robert, Gabriel; Khalfa, Stéphanie; Guedj, Eric; Blin, Olivier; Weinberger, Daniel R.; et al.
Abstract Converging evidence points to a link between anxiety proneness and altered emotional functioning, including threat‐related biases in selective attention and higher susceptibility to emotionally ambiguous stimuli. However, during these complex emotional situations, it remains unclear how trait anxiety affects the engagement of the prefrontal emotional control system and particularly the anterior cingulate cortex (ACC), a core region at the intersection of the limbic and prefrontal systems. Using an emotional conflict task and functional magnetic resonance imaging (fMRI), we investigated in healthy subjects the relations between trait anxiety and both regional activity and functional connectivity (psychophysiological interaction) of the ACC. Higher levels of anxiety were associated with stronger task‐related activation in ACC but with reduced functional connectivity between ACC and lateral prefrontal cortex (LPFC). These results support the hypothesis that when one is faced with emotionally incompatible information, anxiety leads to inefficient high‐order control, characterized by insufficient ACC‐LPFC functional coupling and increases, possibly compensatory, in activation of ACC. Our findings provide a deeper understanding of the pathophysiology of the neural circuitry underlying anxiety and may offer potential treatment markers for anxiety disorders. Hum Brain Mapp 36:2207–2214, 2015. © 2015 Wiley Periodicals, Inc.